Trends in Politeness Research in Indonesian Language Education Journals: A Decade of Insights (2013–2023) - Fuadin, Ahmad; Syihabuddin, Syihabuddin; Hidayat, Mupid; Mulyati, Yeti (Jurnal Pendidikan Progresif, 2025)
Abstract: Trends in Politeness Research in Indonesian Language Education Journals: A Decade of Insights (2013–2023). Objective: Linguistic politeness is a crucial element in communication that reflects cultural norms and social values, particularly in multicultural societies like Indonesia. This study aims to analyze trends in politeness research within Indonesian language and literature education journals indexed in SINTA during 2013–2023. Methods: Employing a qualitative descriptive approach and the Systematic Literature Review (SLR) method, this research examines 63 articles based on publication volume, research methods, focus areas, theoretical adaptations, and practical implications. Articles were selected using the keywords "politeness" and "linguistic politeness" through a systematic screening process aligned with inclusion criteria, including relevance to the context of language and literature education. Thematic analysis was applied to identify patterns, key trends, and shifts in research focus. Findings: The findings reveal a significant increase in publications between 2019 and 2023, driven by the expansion of digital platforms and the rise of online learning due to the COVID-19 pandemic. Most studies employed qualitative descriptive methods, focusing on middle school students in formal education contexts. Additionally, there has been growing attention to politeness issues in digital interactions, particularly concerning phenomena like hate speech and trolling. The study also highlights the dominance of international politeness theories, such as those by Brown and Levinson, which have been modified to reflect Indonesia's cultural diversity and social norms. This underscores the need for more excellent localization of global theories. Conclusion: As a recommendation, diversifying research methodologies by incorporating quantitative and mixed methods approaches is strongly advised to provide a more comprehensive understanding of politeness dynamics. Furthermore, integrating politeness education into curricula is essential to promote courteous communication in multicultural and digital contexts. This research contributes to the theoretical discourse by enriching discussions on linguistic politeness and offers practical strategies for fostering harmonious communication in traditional and digital environments. studies. Keywords: content analysis, education journals, indonesian language, politeness research, research trends.